2021
DOI: 10.1111/1750-3841.15659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and pH on the gelation, rheology, texture, and structural properties of whey protein and sugar gels based on Maillard reaction

Abstract: This study aimed to determine the effect of initial pH and temperature on whey protein gel formation via the Maillard reaction, including changes in gel structure, rheological and texture properties. The color changes in the whey protein and glucose gels were not significant with increasing heat temperature. High temperature and alkaline conditions promoted exposure to hydrophobic groups such as -SH, which accelerated protein aggregation and gel formation. Moreover, the increased particle size and additional h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…[45]. These results are directly proportional to previous research conducted by [46], where hardness of the whey protein gel has a higher value at 70 o C than 60 and 65 o C. According to [47], the pH of the solution is a crucial factor affecting the appearance and strength of the WPC gel.…”
Section: Gel Texture Characteristicssupporting
confidence: 67%
“…[45]. These results are directly proportional to previous research conducted by [46], where hardness of the whey protein gel has a higher value at 70 o C than 60 and 65 o C. According to [47], the pH of the solution is a crucial factor affecting the appearance and strength of the WPC gel.…”
Section: Gel Texture Characteristicssupporting
confidence: 67%
“…The double emulsion particle size and PDI increased significantly at 70 °C and formed a gel at 90 °C. This may allow the whey proteins to form a stable gel network through aggregation and exchange under thermal induction, which disrupts the interfacial layer, thus allowing gradual gelling of the emulsion [48] . With the increase in temperature, the absolute zeta potential value of the double emulsion decreased significantly from 23.30 ± 0.35 mV to 22.33 ± 0.46 mV, indicating that the heat treatment had a similar effect on the zeta potential of the double emulsion.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Nonetheless, the membrane filtration system for whey faces a challenge related to fouling, which is directly linked to the economic sustainability of these systems. 11 Fouling occurs when whey molecules or aggregates deposit on the membrane surface or within its pores, gradually obstructing them and impeding filtration. 12 It is characterized by a progressive decline in permeate flow over time during constant-pressure operation or an increase in transmembrane pressure during constant filtration flow operation.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Mitigation methods include the application of external forces such as sonication, heating, electric and magnetic fields, pretreatment of the protein solution through ozonation, chlorination, and aeration, addition of chemicals, dynamic membrane formation via particle deposition, which acts as a secondary membrane reducing protein-membrane interaction, alteration of hydrodynamics using spacers, pulsatile flow, or periodic flow reversal, and finally, enzymatic pretreatment of the feed by adding the transglutaminase (TGase) enzyme. 11,14 Enzymatic cross-linking is sparsely documented in the scientific literature, yet studies have revealed promising results related to increased permeate flux and protein concentration. [11][12][13]15,16 This technique promotes cross-links between lysine and glutamine residues, increasing the molecule's size and facilitating its retention in the filtration membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation